Perlindungan Hukum Terhadap Nazhir dari Tuntutan Ahli Waris Atas Akta Ikrar Wakaf Yang Dibuat Dihadapan Pejabat Pembuat Akta Ikrar Wakaf (PPAIW) - Desy Trihartini; Anriz Nazaruddin Halim; Erny Kencanawati (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
This study aims to evaluate and analyze the legal repercussions of the waqf pledge deed executed prior to the official waqf pledge deed (PPAIW), as well as the legal protection of waqf beneficiaries (nadzir) on the requests of the heirs of the waqf donor (wakif). The research offered is normative legal research. This research utilizes the standard legal process as its methodology. This study adopts a qualitative methodology for data analysis. These are the results of this research: (1) The Waqf Pledge Deed is legal under Islamic law and domestic law (Positive law). In accordance with Islamic law, waqf must meet the pillars and requirements of waqf, which include the existence of waqif, nadzir, waqf property, the intention of using the object as waqf, and waqf pledge from wakif to nadzir. Waqf must meet the following requirements to be valid under national law (positive law): existence of wakif, nadzir, waqf property, waqf pledge, and naming of waqf items. Consequently, the Waqf Pledge Deed is legal under both Islamic law and American law. (2) The execution of the Waqf Pledge Deed, which is followed by the registration of waqf land for the purpose of issuing a waqf land certificate, affords Nadzir legal protection and legal certainty in the administration of waqf land. The existence of a Waqf Pledge Deed performed in accordance with its conditions, followed by the registration of waqf land at the local Land Office for the issuance of a Waqf Land Certificate, offers Nadzir, who receives and manages waqf land, legal protection and legal guarantee.